Metal surface alloying treatment method, metal interconnection layer side wall alloying treatment method, metal interconnection layer and display panel
Electrolytic treatment with acidic electrolyte and thiocarboxylic acid inhibitors solved the problem of sidewall corrosion in the metal interconnect layer, formed a uniform alloy layer, improved the performance and lifespan of the metal interconnect layer, and simplified the process.
Patent Information
- Application Number
- CN202512000646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-26
- Publication Date
- 2026-03-20
AI Technical Summary
In the prior art, the sidewall alloying treatment of metal interconnect layers is not very effective, especially the sidewall corrosion problem of Ti-Al-Ti layer units, which leads to a decline in the performance of metal interconnect layers.
An acidic electrolyte is used for electrolytic treatment, and a thiocarboxylic acid inhibitor is added. A uniform alloy layer is formed through electrolytic deposition. The reaction progress is controlled to form a uniform alloy layer, avoiding high-temperature treatment and over-alloying.
It achieves uniform distribution and high alloying degree of alloy layer, improves service life of metal interconnect layer, simplifies process flow and avoids damage to organic materials caused by high temperature treatment.
Smart Images

Figure CN121700474A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of metal surface treatment technology, and in particular to a method for alloying metal surfaces, a method for alloying the sidewalls of metal interconnect layers, a metal interconnect layer, and a display panel. Background Technology
[0002] In light-emitting diode (OLED) displays, the backplane of thin-film transistors (TFTs) houses gate or source / drain devices, often referred to as array layers and metal layers during manufacturing and design. In OLED displays, these are collectively called metal interconnect layers, whose primary functions are conductivity and circuit control. Metal interconnect layers are typically composed of a large number of patterned metal interconnect units, with grooves formed between adjacent units to accommodate circuitry. These metal interconnect layers are generally fabricated by etching multiple stacked metal layers. The most common metal layer structure is a three-layer structure: titanium-aluminum-titanium (Ti-Al-Ti). The top Ti layer acts as an etching barrier, process compatibility layer, or protective layer; the middle Al layer is a conductive layer; and the bottom Ti layer can directly contact the organic material layer.
[0003] However, after etching, the sidewalls of these metal interconnect units are prone to corrosion due to the formation of galvanic systems caused by differences in metal activity. For example, in the sidewalls of Ti-Al-Ti layer units, aluminum has higher metal activity than titanium, and the formation of galvanic systems makes the aluminum edges more susceptible to corrosion, affecting the performance of the entire metal interconnect layer. Therefore, existing technologies often alloy the sidewalls of the metal interconnect units to reduce corrosion. However, common technical solutions have some problems, resulting in poor alloying effects on the sidewalls of the metal interconnect layers. Summary of the Invention
[0004] The purpose of this application is to provide a method for alloying metal surfaces, a method for alloying metal interconnect layer sidewalls, a metal interconnect layer, and a display panel, in order to solve the problem of poor performance of existing metal interconnect layer sidewall alloying methods.
[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a method for alloying a metal surface, comprising the following steps: An acidic electrolyte containing a first metal ion is prepared, and the electrolyte is electrolyzed using a second metal as the cathode. During the electrolytic process, inhibitors are added to the electrolyte; Among them, the inhibitors include thiocarboxylic acid materials, and the reducing power of the second metal is higher than that of hydrogen.
[0006] In the alloying method of this application, the first metal ions are first reduced on the cathode surface and deposited to form a loose first metal. Simultaneously, a small amount of second metal ions dissolve in the acidic electrolyte environment. These second metal ions diffuse outwards and continuously co-deposit with the first metal ions at the atomic level under electrolysis. As the diffusion of the second metal ions and the co-deposition of the two metal ions proceed synchronously, the loose first metal and the further co-deposited metals gradually form a uniform alloy layer, achieving alloying treatment of the second metal surface. During the electrolytic treatment, the addition of inhibitors causes the thiocarboxylic acid materials to gradually decompose, and the dielectric constant of the electrolyte gradually decreases. When the dielectric constant drops to a certain value, the concentration of decomposition products also reaches a critical point, and the co-deposition reaction of the two metal ions automatically terminates, preventing further deposition. This allows control over the electrochemical reaction progress, giving the alloying treatment good self-limiting properties, eliminating the need for continuous monitoring of the alloy layer formation progress. Therefore, this method does not require high-temperature treatment, the alloying effect is controllable and stable, and the alloy layer has a uniform elemental distribution, high alloying degree, and uniform thickness, effectively protecting the second metal.
[0007] Optionally, the first metal ion includes at least one of titanium ions and molybdenum ions.
[0008] Optionally, the second metal includes aluminum.
[0009] Optionally, an inhibitor may be added to the electrolyte when the total electrolysis time is 60% to 70%.
[0010] Optionally, the thiocarboxylic acid materials include at least one of thiomalic acid, thiosalicylic acid, and mercaptosuccinic acid.
[0011] Optionally, the electrolysis process may further include a step of applying ultrasound to the electrolyte.
[0012] Optionally, when an inhibitor is added to the electrolyte, the concentration of the inhibitor in the electrolyte is 0.05 mol / L to 0.15 mol / L.
[0013] Optionally, after adding an inhibitor to the electrolyte, the electrolyte is heated to a temperature of 55°C to 90°C.
[0014] Optionally, the first metal ion includes titanium ions, and the prepared electrolyte satisfies at least one of the following characteristics: (1) The concentration of titanium ions is 0.05 mol / L to 0.3 mol / L; (2) The electrolyte contains a complexing agent and an alcohol solvent; (3) The pH value of the electrolyte is 4.0 to 4.5; (4) The solute in the electrolyte includes at least one of titanium tetrachloride and titanium trichloride.
[0015] Optionally, the complexing agent includes at least one of ethylenediaminetetraacetic acid, triethanolamine, citric acid, and citrate.
[0016] Optionally, the alcohol solvent includes at least one of isopropanol and ethylene glycol.
[0017] Optionally, the molar ratio of the first metal ion to the complexing agent is 1:(4 to 8.5).
[0018] Optionally, the electrolytic treatment includes a periodic energizing process, each cycle comprising sequentially applying a first negative voltage, a second negative voltage, and a positive voltage, and satisfying at least one of the following characteristics: (1) The absolute values of the first negative voltage, the second negative voltage, and the positive voltage decrease sequentially; (2) The duration of applying the first negative voltage is 0.1 s to 0.3 s; (3) The duration of applying the second negative voltage is 0.2 s to 0.6 s; (4) The duration of applying the positive voltage is 0.1 s to 0.3 s; (5) The periodic power-on process includes 40 to 60 cycles.
[0019] Optionally, the current type for electrolytic treatment includes pulsed current, which satisfies at least one of the following characteristics: (1) Peak current density is -27 mA / cm 2 ~-23 mA / cm 2 ; (2) The width of a single pulse current is 8 ms to 12 ms; (3) The duty cycle of the reverse pulse is 30% to 70%.
[0020] Secondly, this application provides a method for alloying the sidewalls of a metal interconnect layer, comprising the following steps: A metal interconnect layer cell to be processed is provided, the metal interconnect layer cell to be processed includes a first layer, a second layer and a third layer stacked sequentially along the thickness direction; The sidewalls of the metal interconnect layer unit to be treated are processed according to the metal surface alloying treatment method of this application described above; The first and third layers contain the metal corresponding to the first metal ion, and the second layer contains the second metal.
[0021] This application's metal interconnect layer sidewall alloying treatment method employs the aforementioned metal surface alloying treatment method. In this method, the first layer of the metal interconnect layer unit is a protective layer, the second layer is a conductive layer, and the third layer is an electron injection layer that directly contacts the organic light-emitting material. Through a wet electrolytic process, an alloy layer of the first and second metals is formed on the sidewall of the second layer. This helps protect the second layer, reduces corrosion on its sidewalls, and improves the lifespan of the metal interconnect layer. Furthermore, traditional sputtering deposition alloying methods require high-temperature treatment, which can easily damage the organic light-emitting material, and often require the deposition of a second metal layer as a transition layer. In contrast, this application's method not only eliminates the need for high-temperature treatment but also directly utilizes the second layer itself as a metal source, reducing the number of steps. Traditional chemical alloying methods struggle to control the reaction progress, leading to over-alloying and problems such as uneven alloying degree and uneven alloy layer thickness. This application's method, however, forms a uniform alloy layer through electrolytic treatment and incorporates specific inhibitors, making the alloying reaction progress controllable and exhibiting good self-limiting properties, eliminating the need for continuous monitoring of the alloy layer formation progress.
[0022] Optionally, the thickness of the first layer is 0.05 μm to 0.2 μm.
[0023] Optionally, the thickness of the second layer is 0.2 μm to 1 μm.
[0024] Optionally, the thickness of the third layer is 0.05 μm to 0.2 μm.
[0025] Optionally, the metal interconnect layer unit to be processed is obtained by etching a metal interconnect board.
[0026] Thirdly, this application provides a metal interconnect layer, including a plurality of sidewall alloyed metal interconnect layer units, which are obtained by the metal interconnect layer sidewall alloying treatment method described above. The sidewall alloyed metal interconnect unit includes a first layer, a second layer, and a third layer stacked sequentially along the thickness direction; Furthermore, at least the sidewall of the second layer is provided with an alloy layer.
[0027] The metal interconnect layer unit with sidewall alloying of the metal interconnect layer in this application has been treated by the above-mentioned metal interconnect layer sidewall alloying treatment method, so an alloy layer is formed on the sidewall of the metal interconnect layer unit. The alloy layer can effectively inhibit the corrosion of the sidewall of the metal interconnect layer unit and improve the service life of the metal interconnect layer.
[0028] Fourthly, this application provides a display panel including the aforementioned metal interconnect layer.
[0029] The display panel in this embodiment includes the aforementioned metal interconnect layer. The metal interconnect layer has a long service life; therefore, the display panel also has a long service life. This display panel can be applied to various mobile communication and electronic terminal products, such as smartphones, smartwatches, tablets, and laptops. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a schematic diagram of the structure of several metal interconnect layer units to be processed in Embodiment 1 of this application; Figure 2 This is a schematic diagram of the structure of several metal interconnect layer units after the sidewall alloying treatment in Embodiment 1 of this application; Figure 3 This is a schematic diagram of applying a periodically varying voltage to the cathode during the electrolytic treatment process of Embodiment 1 of this application; Figure 4 This is a schematic diagram of the pulse current used in the electrolytic treatment process of Embodiment 1 of this application; Figure 5 This is a high-resolution XPS spectrum of Ti 2P in the sidewall alloy of Example 1 of this application; Figure 6 This is a high-resolution XPS spectrum of Al 2P for the sidewall alloy of Example 1 of this application.
[0032] Figure label: 1-First layer; 2-Second layer; 3-Third layer; 4-Alloy layer. Detailed Implementation
[0033] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0034] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0035] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions mean any combination of these items, including any combination of single or multiple items.
[0036] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0037] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as µg, mg, g, or kg.
[0038] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, a first feature may also be referred to as a second feature, and similarly, a second feature may also be referred to as a first feature. Thus, a feature defined with "first" and "second" may explicitly or implicitly include one or more of that feature.
[0039] Existing alloying methods for the sidewalls of metal interconnect layers in OLED display devices suffer from several problems, resulting in unsatisfactory treatment outcomes. Taking a Ti-Al-Ti interlayer as an example, an aluminum-titanium alloy layer is typically placed on the sidewall of the Al layer to enhance its resistance to galvanic corrosion. If sputtering deposition alloying is used, on the one hand, high-temperature treatment (e.g., 350°C) is often required, which can easily cause thermal damage to the OLED organic light-emitting material directly contacting the underlying Ti layer; on the other hand, an aluminum layer is often pre-deposited on the sidewall as a transition layer or underlayer before further alloy layer deposition, making the process cumbersome. If chemical alloying methods are used, it is difficult to control the reaction progress, leading to over-alloying, which affects the performance of the Al layer itself, and also results in uneven alloying degree and uneven alloy layer thickness. Therefore, a metal surface alloying method suitable for the fabrication process and structural system of the metal interconnect layer is needed.
[0040] The dielectric constant used in this application refers to the relative dielectric constant, which is a dimensionless unit.
[0041] The first aspect of this application provides a method for alloying a metal surface, including the following steps S01 to S02: S01: Prepare an acidic electrolyte containing the first metal ions, and electrolyze the electrolyte using the second metal as the cathode. The reducing power of the second metal is higher than that of hydrogen. This can be referred to in the common metal reducing power order table or the standard electrode potential table. The electrode potential of the second metal is lower than that of hydrogen ions. S02: During the electrolysis process, inhibitors are added to the electrolyte. Inhibitors include thiocarboxylic acid materials.
[0042] In the alloying method of this application embodiment, the first metal ions are first reduced on the cathode surface and deposited to form a loose first metal. Simultaneously, a small amount of second metal ions dissolve in the acidic electrolyte environment. During the outward diffusion of these second metal ions, they continuously co-deposit with the first metal ions at the atomic level under electrolysis. As the diffusion of the second metal ions and the co-deposition of the two metal ions proceed synchronously, the loose first metal and the further co-deposited metals gradually form a uniform alloy layer, achieving alloying treatment of the second metal surface. When an inhibitor is added during the electrolytic treatment, the thiocarboxylic acid materials gradually decompose, and the dielectric constant of the electrolyte gradually decreases. When the dielectric constant drops to a certain value, the concentration of decomposition products also reaches a critical point, and the co-deposition reaction of the two metal ions automatically terminates, preventing further deposition. This allows control over the electrochemical reaction progress, giving the alloying treatment good self-limiting properties, eliminating the need for continuous monitoring of the alloy layer formation progress. Therefore, this method does not require high-temperature treatment, the alloying effect is controllable and stable, and the alloy layer has a uniform elemental distribution, high alloying degree, and uniform thickness, effectively protecting the second metal.
[0043] Existing sputtering deposition methods require high-temperature processing, while the processing method of this application does not. Existing sputtering deposition methods require pre-depositing a transition layer to improve the bonding strength between the alloy layer and the metal substrate. However, the processing method of this application, during electrolytic processing, first deposits a first metal and then transforms it into an alloy. Combined with the outward diffusion of second metal ions, the bonding area between the alloy layer and the second metal surface grows continuously and dynamically under the dual effect of these two processes, which is beneficial for enhancing the bonding strength between the two interfaces. Furthermore, by directly utilizing the second metal itself, a strong bond can be achieved without pre-depositing a transition layer, simplifying the process flow. Compared to other chemical alloying schemes, the processing method of this application allows for control of the reaction progress and achieves a high degree of alloying and uniform alloy layer thickness.
[0044] In the metal surface alloying treatment method, the electrolytic treatment of the electrolyte is maintained. Therefore, electrolytic treatment is carried out in both steps S01 and S02. In step S02, an inhibitor is added during the entire electrolytic treatment process. The following will describe the electrolyte, cathode, anode, energizing process, and inhibitor in the electrolytic treatment.
[0045] Regarding electrolytes in electrolytic processing.
[0046] The electrolyte is acidic and is formulated from a first metal ion and other raw materials. In some embodiments, the first metal ion may include at least one of titanium ions and molybdenum ions, preferably titanium ions. These first metal ions can be electrolytically deposited to form a first metal, or co-deposited with second metal ions to form an alloy layer, thereby improving the protection of the second metal surface. The solute used to formulate the first metal ions into the electrolyte may include, but is not limited to, soluble salts of these first metal elements. In an exemplary example, the first metal ion includes titanium ions, and the solute in the electrolyte may include, but is not limited to, at least one of titanium tetrachloride and titanium trichloride. These soluble salts can provide the corresponding titanium ions for electrolytic treatment. In the example, the concentration of titanium ions in the prepared electrolyte can be from 0.05 mol / L to 0.3 mol / L, including but not limited to any value or any two of 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, and 0.3 mol / L. These concentration ranges are beneficial for the electrolyte to stably provide titanium ions for deposition during the electrolytic deposition process, while reducing the phenomenon of excessively fast deposition rate due to excessively high concentration, and reducing the impact on the uniformity of the alloy layer.
[0047] First-order metal ions, such as tetravalent titanium ions, readily hydrolyze in acidic aqueous solutions to form hydroxides, oxides, and other components, causing the electrolyte to become turbid or even precipitate, which easily affects the stability and ionic conductivity of the electrolyte. For example, tetravalent titanium ions readily form titanyl ions in aqueous solutions with a pH of 0.8–2.5, further forming dimers, and finally generating titanium dioxide. The entire process can be simplified to the following hydrolysis reaction: TiCl4 + 2H2O → TiO2 + 4HCl Therefore, in some embodiments, the prepared electrolyte includes a complexing agent and an alcohol solvent. Adding a complexing agent facilitates the formation of a stable complex with the first metal ion, suppresses hydrolysis side reactions, improves the stability of the electrolyte, and is beneficial for subsequent electrolytic deposition. In some embodiments, the complexing agent includes, but is not limited to, at least one of ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), citric acid, and citrate. These complexing agents all contain organic polydentate ligand groups, which can form stable complexes with metal ions and are environmentally friendly. Among them, the molecules of complexing agents such as EDTA and citric acid include multiple negatively charged carboxylate groups, which can coordinate with and bind and protect the positively charged titanium ions, reducing the occurrence of side reactions when the first metal ion contacts water molecules. TEA not only acts as an organic ligand to form a stable complex with the first metal ion but also has weak basicity, further improving the stability of the first metal ion in the electrolyte, analogous to the effect of applying a protective film. Optionally, the combined use of EDTA and TEA can significantly inhibit the hydrolysis reaction of the first metal ion. The synergistic effect of the two complexing agents can promote the formation of ultrastable complexes, such as Ti(EDTA)(TEA)2. 2- It can prevent more than 99% of the first metal ions from hydrolyzing.
[0048] In some embodiments, the molar ratio of the first metal ion to the complexing agent can be 1:(4-8.5), and may include, but is not limited to, any ratio or any two of 1:4, 1:5, 1:6, 1:7, 1:8, and 1:8.5. Within this molar ratio range, the complexing agent can adequately coordinate the first metal ion, reducing the occurrence of hydrolysis. If the amount of complexing agent is too low, it may lead to insufficient complexation and limited effect in inhibiting hydrolysis; if the amount of complexing agent is too high, it may lead to excessive organic matter, affecting the ion migration rate of the electrolyte, thereby reducing the deposition efficiency and the performance of the alloy layer. Optionally, when preparing the electrolyte, the molar ratio of the first metal ion to EDTA and TEA can be 1:(1.5-2.5):(2.5-6), and may include, but is not limited to, any ratio or any two of 1:(1.5 or 2 or 2.5):(2.5 or 3 or 4 or 5 or 6), which is beneficial for further forming a superstable complex and reducing the occurrence of hydrolysis.
[0049] Alcohol solvents generally have good compatibility with water, and adding an alcohol solvent helps reduce the water content in the electrolyte. They can also participate in coordination to some extent and reduce the swelling of organic light-emitting materials, thus enhancing the stability of the complex. These effects are beneficial for further inhibiting the hydrolysis reaction of the first metal ion. In some embodiments, the alcohol solvent may include at least one of isopropanol and ethylene glycol. Isopropanol is typically used as a solvent, and it can be prepared by reacting isopropanol with water at a volume ratio of 1:(2.5–5). This volume ratio can include, but is not limited to, any ratio or a range between any two of 1:2.5, 1:3, 1:4, and 1:5. The solubility parameter δ can be 22.5 MPa. 1 / 2 Ethylene glycol contains two hydroxyl groups, which have the functions of both solvent and cooperating in coordination. In the example, the molar ratio of the first metal ion to EDTA, TEA and ethylene glycol can be 1: (1.5-2.5): (2.5-6): (30-70).
[0050] In step S01, the preparation of the electrolyte may include the following steps: mixing the raw material containing the first metal ion and the solvent thoroughly in a certain proportion; the complexing agent may be further added to the raw material to obtain the electrolyte. In an example, the above components may be mixed in a water bath at 25°C–45°C and stirred thoroughly for 1–3 hours to allow the complexation reaction to proceed fully, forming a stable solution system, resulting in a clear and transparent complexing agent solution that can be stored for more than 48 hours, thus obtaining the electrolyte.
[0051] In some embodiments, the pH value of the prepared electrolyte can be 4.0 to 4.5, including but not limited to any value or a range between any two of 4.0, 4.2, 4.4, and 4.5. Within this pH range, the complexing agent has a strong coordination ability for the first metal ion, and it also facilitates the dissolution of the second metal into ions in the electrolyte, which diffuses and co-deposits with the first metal ion during the electrolysis process.
[0052] Regarding the cathode in electrolytic processing.
[0053] During electrolytic processing, metal ions are reduced and deposited at the cathode. Therefore, using a second metal as the cathode allows for surface alloying, and the second metal can be electrically connected to the negative terminal of the power supply. In some embodiments, the second metal includes aluminum. Aluminum has higher reducing power than hydrogen, so it can dissolve corresponding ions in acidic electrolytes and is commonly used as a conductive layer in metal interconnects. Through diffusion and co-deposition with the first metal ions, an alloy layer tightly bonded to the surface of the second metal is formed, achieving surface alloying of the second metal and improving its protective effect.
[0054] Regarding the anode in electrolytic processing.
[0055] In this embodiment, the anode can be electrically connected to the positive terminal of the power supply, and its material can include, but is not limited to, electrochemically stable noble metals such as Pt and Au, or these materials can be used as the anode of the coating, which helps to reduce the interference of impurities on the electrolytic reaction and reduce the impact on the alloying effect.
[0056] Regarding the energizing process in electrolysis.
[0057] Applying current to the electrolyte through the cathode and anode allows for the deposition of metal ions. The type of current can include, but is not limited to, direct current (DC), pulsed current, or periodically commutated current. Direct current tends to cause metal ions to continuously accumulate on the formed crystal nuclei, a phenomenon known as the tip effect. This can easily lead to dendrite-like or micro-island structures, resulting in voids and affecting the protective effect of the alloy layer on the second metal. Furthermore, the continuous consumption of the first metal ions near the cathode can easily lead to concentration polarization when the ion conduction rate in the electrolyte is insufficient to compensate for the consumption rate. Pulsed current, due to its periodic on / off characteristics, and periodically commutated current, due to its alternating switching between forward and reverse currents, can effectively alleviate ion concentration polarization, promote uniform metal ion deposition, and facilitate the control of the deposition rate.
[0058] In some embodiments, the electrolytic treatment includes periodic energizing, with each cycle involving the sequential application of a negative voltage and a positive voltage. Applying a negative voltage involves applying a negative potential to the second metal, making it the cathode. Metal ions nucleate and grow at the cathode, eventually depositing as metal. Applying a positive voltage involves applying a positive potential to the second metal for a short period, causing a small amount of the deposited metal to dissolve into the electrolyte. It also desorbs bubbles or impurities adhering to the surface of the second metal, resulting in a smoother and cleaner surface. This smooths the deposited layer, reduces surface roughness, and helps alleviate concentration polarization in the electrolyte. Furthermore, the periodic energizing method facilitates the deposition of the first metal ions into a loose, porous nanocluster structure, rather than a dense structure, allowing the electrolyte to flow through it and providing a channel for the dissolution and diffusion of the second metal in the electrolyte.
[0059] Furthermore, each cycle can sequentially apply a first negative voltage, a second negative voltage, and a positive voltage, which can be understood as the nucleation stage, the growth stage, and the desorption stage, respectively.
[0060] In some embodiments, the absolute values of the first negative voltage, the second negative voltage, and the positive voltage can decrease sequentially. Similarly, the absolute values of their current densities can also decrease sequentially. The beneficial effects of this energizing method are: a higher first negative voltage facilitates the rapid formation of numerous fine crystal nuclei by the first metal ions on the second metal surface; a moderate second negative voltage allows the first metal ions to deposit and grow on the crystal nuclei, stably and continuously growing and uniformly covering the second metal surface; and the lowest positive voltage smooths the deposited layer and alleviates concentration polarization in the electrolyte while minimizing excessive dissolution of the deposited metal. In an example, the first negative voltage can be -2.8 V to -2.2 V, including but not limited to any value or any two of -2.8 V, -2.6 V, -2.4 V, and -2.2 V, and the average current density can be -25 mA / cm². 2 The second negative voltage can be -1.4 V to -1.0 V, and can include, but is not limited to, any value or any two of -1.4 V, -1.2 V, and -1.0 V. The positive voltage can be 0.6 V to 1.0 V, and can include, but is not limited to, any value or any two of 0.6 V, 0.8 V, and 1.0 V.
[0061] Accordingly, regarding the duration of applying the first negative voltage, the second negative voltage, and the positive voltage, the duration of applying the first negative voltage can be 0.1 s to 0.3 s, and can include, but is not limited to, any value or a range between any two of 0.1 s, 0.15 s, 0.2 s, 0.25 s, and 0.3 s; the duration of applying the second negative voltage can be 0.2 s to 0.6 s, and can include, but is not limited to, any value or a range between any two of 0.2 s, 0.3 s, 0.4 s, 0.5 s, and 0.6 s; the duration of applying the positive voltage can be 0.1 s to 0.3 s, and can include, but is not limited to, any value or a range between any two of 0.1 s, 0.15 s, 0.2 s, 0.25 s, and 0.3 s. The first negative voltage is applied for a short time, which can control the number of crystal nuclei formed; the second negative voltage is applied for the longest time, which is conducive to promoting the full growth of metal crystals; the positive voltage is also applied for a short time, which minimizes the excessive dissolution of the deposited metal.
[0062] Through the above-described periodic electrostatic treatment, in each cycle, the first metal ions undergo a process of nucleation, crystal growth, and desorption / leveling on the second metal surface. In some embodiments, the periodic electrostatic treatment may include 40 to 60 cycles, including but not limited to any value or a range between any two of 40, 45, 50, 55, and 60 cycles, so that the first metal ions are continuously and uniformly deposited on the second metal surface, forming a loose first metal nanocluster, and the deposited first metal layer is relatively flat.
[0063] In some embodiments, the current type for electrolytic treatment includes pulsed current. This method is particularly suitable for scenarios where the second metal surface is uneven, such as when the second metal surface has defects such as depressions, pores, or protrusions. Continuously applying direct current can easily cause the first metal ions to concentrate at the defects, resulting in uneven deposition rates and making it difficult to form a uniform deposition layer. Pulsed current, by periodically interrupting the current, alleviates concentration polarization in the electrolyte, allowing ion diffusion to recover, effectively suppressing the tip current effect, and thus improving deposition uniformity.
[0064] The waveform of the pulsed current can include, but is not limited to, rectangular waves, triangular waves, sawtooth waves, sine waves, etc., with rectangular waves being a possible choice. The pulse form can include, but is not limited to, single pulses, double pulses, etc., with double pulses being a possible choice. A double pulse consists of a forward pulse and a reverse pulse, and may also include a turn-off period. The pulse timing can include, but is not limited to, forward-turn-off-reverse, forward-reverse-turn-off, and reverse-turn-off-forward patterns. The reverse pulse is used to drive the deposition of the first metal ions on the second metal surface, while the forward pulse dissolves a portion of the deposited layer surface in a short time, their effects analogous to the negative and positive voltages in the aforementioned periodic current-passing process. The turn-off period redistributes the ion concentration in the electrolyte, reducing concentration polarization.
[0065] In some embodiments, the peak current density of the reverse pulse current can be -27 mA / cm². 2 ~-23 mA / cm 2 The current density can be any value or a range between any two of -27 mA / cm², -25 mA / cm², -24 mA / cm², and -23 mA / cm², with -25 mA / cm² being a suitable choice. These parameters help control the deposition rate, preventing slow deposition due to excessively low current density and uneven deposition due to excessively high current density. The absolute value of the peak current density of the forward pulse current can be smaller than the absolute value of the peak current density of the reverse pulse current, allowing deposition to dominate while also ensuring a smoothing effect. The width of a single pulse current is 8 ms to 12 ms, and can be any value or a range between any two of 8 ms, 9 ms, 10 ms, 11 ms, and 12 ms. This helps maintain pulse stability and controllability of the deposition process. Here, the pulse current width refers to the duration of a segment of current in the same direction within the pulse. For example, in a set of forward-off-reverse pulse currents, the width of a single pulse refers to the duration of each of the forward, off, and reverse segments.
[0066] During the entire electrolytic process, optionally, the duration of the reverse pulse is longer than that of the forward pulse, allowing the deposition process to dominate while also achieving a leveling effect. In some embodiments, the duty cycle of the reverse pulse can be 30% to 70%, including but not limited to any value or a range between any two of 30%, 40%, 50%, 60%, and 70%. These duty cycles are beneficial for achieving a dynamic balance between deposition and dissolution, and for achieving uniform deposition.
[0067] In some embodiments, the entire electrolysis process is energized using the aforementioned periodic energizing method. Each cycle sequentially applies three stages: a first negative voltage (0.1 s–0.3 s), a second negative voltage (0.2 s–0.6 s), and a positive voltage (0.1 s–0.3 s), for a total of 40–60 cycles. Each stage is performed using pulsed current, with a single pulse width of 8 ms–12 ms. Each stage contains dozens or even hundreds of pulse currents. The pulse current for each stage can be adjusted based on the voltage value, required current density, and current direction. Parameters such as pulse frequency, duty cycle, on / off time, and peak current can be adjusted to match the pulse current with the overall parameters required for each stage. For example, in the positive voltage stage, the pulse current is predominantly positive pulses. Those skilled in the art can make corresponding adjustments based on the above description. This multi-stage pulse sequence processing method facilitates more precise deposition control.
[0068] In some embodiments, the electrolysis process further includes applying ultrasound to the electrolyte. Applying ultrasound accelerates the migration of metal ions in the electrolyte, reducing concentration polarization; it also promotes uniform distribution of metal ions, reducing the formation of dendrites, micro-island structures, and other morphologies due to tip effects during deposition, and reducing voids and other defects—both of which contribute to uniform deposition. Furthermore, it helps eliminate bubble adhesion to the second metal surface, reducing deposition defects. In some embodiments, the power of the ultrasound can be 20 W to 80 W, including but not limited to any value or any two of 20 W, 40 W, 60 W, and 80 W; the frequency of the ultrasound can be 1.5 MHz to 5 MHz, including but not limited to any value or any two of 1.5 MHz, 2 MHz, 3 MHz, 4 MHz, and 5 MHz. These ultrasound parameters promote uniform deposition of metal ions.
[0069] Regarding the inhibitor in step S02.
[0070] The inhibitors in the processing method of this application include thiocarboxylic acid materials. These materials contain thiol and carboxyl groups, which gradually decompose in an acidic electrolyte at a certain temperature to generate hydrogen sulfide. When the electrolyte contains alcohols, the carboxyl groups may also undergo esterification reactions with the alcohols. As described above, the addition of these materials results in a higher dielectric constant in the electrolyte. As the materials gradually react with the acidic electrolyte, the generated hydrogen sulfide overflows from the electrolyte, and the dielectric constant of the electrolyte gradually decreases. When the dielectric constant of the electrolyte decreases to a certain value, the concentration of decomposition products also reaches a critical point, and the co-deposition reaction of the two metal ions automatically terminates, preventing further deposition. This allows for control of the electrochemical reaction progress, giving the alloying process good self-limiting properties and eliminating the need for continuous monitoring of the alloy layer formation progress. The endpoint value of this dielectric constant can be 20–26, and can be selected as 25.
[0071] In some embodiments, the thiocarboxylic acid materials include at least one of thiomalic acid, thiosalicylic acid, and mercaptosuccinic acid, with thiomalic acid being the preferred choice. These thiocarboxylic acid materials contain thiol and carboxyl groups, which can achieve the aforementioned effect of controlling the progress of the electrochemical reaction. Thiomalic acid, in particular, contains one thiol group and two carboxyl groups, allowing for controllable reaction rates and producing more environmentally friendly reaction products. In some embodiments, when an inhibitor is added to the electrolyte, the concentration of the inhibitor in the electrolyte is 0.05 mol / L to 0.15 mol / L, including but not limited to any value or any two of 0.05 mol / L, 0.07 mol / L, 0.10 mol / L, 0.13 mol / L, and 0.15 mol / L. This concentration range effectively controls the reaction rate while avoiding excessively long processing times due to over-introduction. As the reaction proceeds, the concentration of the inhibitor gradually decreases until the reaction is complete.
[0072] In some embodiments, the temperature of the electrolyte before adding the inhibitor can be room temperature, or between 15°C and 40°C. After adding the inhibitor, the electrolyte is heated to a temperature of 55°C to 90°C, including but not limited to any value or a range between any two of 55°C, 60°C, 70°C, 80°C, and 90°C. Thiocarboxylic acid materials such as thiomalic acid will gradually decompose at the above temperatures. For example, if thiomalic acid begins to decompose above 55°C, it will accelerate the generation of hydrogen sulfide and its escape from the electrolyte, causing the dielectric constant of the electrolyte to gradually decrease, thus achieving controllable reaction progress and avoiding other side reactions caused by excessively high temperatures.
[0073] In the initial stage of electrolytic treatment, the first metal ions are deposited to form loose first metal nanoclusters, forming a first metal layer on the surface of the second metal. Subsequently, with the dissolution and ion diffusion of the second metal, as well as the co-deposition of the two metal ions, an alloy layer gradually forms on the surface of the second metal. As mentioned above, this method is beneficial for improving the bonding strength between the formed alloy layer and the second metal surface. When the initial stage of electrolytic treatment is complete and the first metal ion deposition has reached a certain extent, an inhibitor can be added. Specifically, this can be determined by referring to the thickness of the first metal deposition layer formed by the first metal ion deposition and the electrolytic treatment time. When the thickness of the first metal deposition layer reaches 0.12 μm to 0.5 μm, or when 60% to 70% of the total electrolytic treatment time has elapsed, or when 30 to 40 cycles of the periodic electrolytic treatment method described above have been performed, an inhibitor can be added to the electrolyte to regulate the subsequent co-deposition process. Before and after adding the inhibitor, the relevant parameters of the electrolytic process can be exactly the same or different; both can be referred to the description of the electrolytic process above. Optionally, keeping the electrolytic parameters the same before and after adding the inhibitor is beneficial for maintaining the stability of the electrochemical reaction throughout the electrolytic treatment process. At the end of the entire electrolysis process, an alloy layer forms on the surface of the second metal, which effectively protects it. The thickness of this alloy layer can be 0.2 μm to 0.7 μm, and its coverage on the metal surface can be >98%. Furthermore, the electrolyte is neutral or weakly acidic, and its components have good biodegradability, which also reduces the risk of environmental pollution.
[0074] The metal surface alloying treatment method of this application can be applied to a variety of fields and products, including but not limited to upstream products such as cables, electronic switches, controllers, and bearings. It can also be used to process multi-layer metals of metal interconnect layers and for multi-layer metal processing in capacitive touch control processes (TP processes).
[0075] A second aspect of this application provides a method for alloying the sidewalls of a metal interconnect layer, comprising the following steps G10 to G20: G10: Provides a metal interconnect layer unit to be processed, the metal interconnect layer unit including a first layer, a second layer and a third layer stacked sequentially along the thickness direction; G20: The sidewall of the metal interconnect layer cell to be treated is processed according to the metal surface alloying treatment method of the above-described embodiments of this application; The first and third layers comprise a first metal, and the second layer comprises a second metal.
[0076] The metal interconnect layer sidewall alloying method in this application adopts the aforementioned metal surface alloying method. The first layer of the metal interconnect layer unit is a protective layer, the second layer is a conductive layer, and the third layer is an electron injection layer in direct contact with the organic light-emitting material. Through a wet electrolytic process, an alloy layer of the first and second metals is formed on the sidewall of the second layer. This helps protect the second layer, reduces corrosion on its sidewalls, and improves the lifespan of the metal interconnect layer. Furthermore, traditional sputtering deposition alloying methods require high-temperature treatment, which can easily damage the organic light-emitting material, and often require the deposition of a second metal layer as a transition layer. The method in this application not only eliminates the need for high-temperature treatment but also directly utilizes the second layer itself as a metal source, reducing the number of steps. Traditional chemical alloying methods are difficult to control the reaction progress, leading to over-alloying and problems such as uneven alloying degree and uneven alloy layer thickness. The method in this application forms a uniform alloy layer through electrolytic treatment and incorporates specific inhibitors, making the alloying reaction progress controllable and exhibiting good self-limiting properties, eliminating the need for continuous monitoring of the alloy layer formation progress.
[0077] In step G10, a metal interconnect board to be processed is first provided. The processing method for fabricating metal interconnect layer units from these metal interconnect boards can refer to existing processing methods. In some embodiments, the metal interconnect layer units to be processed are obtained from the metal interconnect board through etching. Generally, a three-layer stacked metal interconnect board is sequentially subjected to photoresist exposure and development, patterning etching with an etchant, or dry etching to form several metal interconnect layer units to be alloyed. The shape of the metal interconnect layer units can be set according to the layout requirements of the pixel array, and these metal interconnect layer units constitute a patterned structure. Grooves are formed between adjacent metal interconnect layer units, and these grooves can be subsequently used to set circuits for functions such as circuit control. For example, in active-matrix organic light-emitting diode (AMOLED) technology, the linewidth of the grooves can be less than 10 μm, and the aspect ratio can be greater than 5:1; the processing method of this application is still applicable.
[0078] In some embodiments, the thickness of the first layer is 0.05 μm to 0.2 μm, and its material may include the aforementioned first metal, optionally Ti. The first layer serves as an etching barrier layer, a process compatibility layer, or a protective layer. During the etching process, it can prevent the second layer from being corroded too quickly, improve reaction controllability, and also help improve the oxidation resistance and long-term stability of the cathode during subsequent packaging, storage, and operation.
[0079] In some embodiments, the thickness of the second layer is 0.05 μm to 0.2 μm, and its material may include the aforementioned second metal, optionally Al. The second layer serves as a conductive layer, providing good electrical connection.
[0080] In some embodiments, the thickness of the third layer is 0.05 μm to 0.2 μm, and its material may include the aforementioned first metal, optionally Ti. The third layer can directly contact the organic material layer, matching the energy level of the organic light-emitting material, while also reducing the direct contact between the conductive layer and the organic light-emitting material, so as to prevent the material of the conductive layer from diffusing into the organic light-emitting layer to form quenching centers, thus reducing luminous efficiency and lifespan.
[0081] Step G20 involves treating the sidewalls of the metal interconnect layer unit to be treated using the aforementioned metal surface alloying treatment method. The preparation of the electrolyte, selection of electrodes, energizing process, and use of inhibitors can all be referenced in the descriptions therein. For example, the electrolyte can be prepared using first metal ions, and complexing agents, alcohols, etc., can be added during preparation. The metal interconnect layer unit to be treated is placed in the electrolyte, with the second layer connected to a power source as the cathode of the electrolytic reaction, and a noble metal electrode as the anode. Since the preparation of metal interconnect layer units generally involves etching, the sidewall surface of the second layer is difficult to achieve absolute flatness, often exhibiting micron-sized trenches. Using conventional electroplating methods such as direct current can cause the first metal ions to accumulate at the trench openings, making it difficult to cover the inside of the trenches, resulting in a coverage rate often less than 80%. Therefore, the energizing process can refer to the aforementioned periodic energizing treatment and pulsed current method. Furthermore, ultrasound can be applied to the electrolyte during the electrolytic treatment process.
[0082] The entire electrolytic process begins with the deposition of the first metal ions. Subsequently, due to the dissolution and diffusion of the second metal and the co-deposition of the two metal ions, an alloy layer is formed on the sidewall of the second layer. Inhibitors are added during the electrolytic process, and the electrolyte is heated, typically via a water bath. As the inhibitors decompose, the dielectric constant of the electrolyte gradually decreases. The dielectric constant can be continuously monitored online. When it drops to a certain value, such as 25, the concentration of decomposition products reaches a critical point, automatically terminating the co-deposition reaction of the two metal ions and forming an alloy layer on the sidewall of the second layer to protect it. The thickness of the alloy layer can be 0.2 μm to 0.7 μm, and the coverage of the second layer sidewall can be >98%. After alloying, the photoresist can be removed. The entire process can be directly integrated into existing wet etching or stripping equipment for OLEDs, adapting to existing processes without requiring complex processes or additional equipment as with existing sidewall alloying technologies.
[0083] A third aspect of this application provides a metal interconnect layer, including a plurality of sidewall alloyed metal interconnect layer units, wherein the sidewall alloyed metal interconnect layer units are obtained by the metal interconnect layer sidewall alloying treatment method described above in this application. The sidewall alloyed metal interconnect unit includes a first layer, a second layer, and a third layer stacked sequentially along the thickness direction; Furthermore, at least the sidewall of the second layer is provided with an alloy layer.
[0084] The metal interconnect layer unit with sidewall alloying in this embodiment has been treated by the above-mentioned metal interconnect layer sidewall alloying treatment method, thus forming an alloy layer on the sidewall of the metal interconnect layer unit. This alloy layer can effectively inhibit corrosion of the sidewall of the metal interconnect layer unit and improve the service life of the metal interconnect layer.
[0085] In the example, the thickness and material type of the first, second, and third layers, alloy layers, and metal interconnect layer units with sidewall alloying can all refer to the description in the metal interconnect layer sidewall alloying treatment method in the second aspect above.
[0086] In the example, the thickness of the first layer can be 0.05 μm to 0.2 μm, and its material can include the aforementioned first metal, optionally Ti. The thickness of the second layer can be 0.05 μm to 0.2 μm, and its material can include the aforementioned second metal, optionally Al. The thickness of the third layer can be 0.05 μm to 0.2 μm, and its material can include the aforementioned first metal, optionally Ti. The thickness of the alloy layer can be 0.2 μm to 0.7 μm, and its coverage of the sidewalls of the second layer can be >98%, and its material can be the aforementioned aluminum-titanium alloy.
[0087] Adjacent sidewall alloyed metal interconnect units are separated by grooves. The linewidth of these grooves can be less than 10 μm, and the aspect ratio can be greater than 5:1. Circuits can be arranged within these grooves. These sidewall alloyed metal interconnect units can be arranged in an array.
[0088] A fourth aspect of this application provides a display panel including the metal interconnect layer described in the above-described embodiments of this application.
[0089] The display panel in this embodiment includes the aforementioned metal interconnect layer. The metal interconnect layer has a long service life; therefore, the display panel also has a long service life. This display panel can be applied to various mobile communication and electronic terminal products, such as smartphones, smartwatches, tablets, and laptops.
[0090] The following description is based on specific embodiments.
[0091] Example 1 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer, including the following steps S1 to S4: S1: Raw Material Preparation First, a metal interconnect board is provided, comprising an upper layer, a middle layer, and a lower layer stacked sequentially along the thickness direction, namely a Ti layer, an Al layer, and a Ti layer, with thicknesses of 0.1 μm, 0.7 μm, and 0.1 μm respectively. The lower layer can directly contact the organic light-emitting material layer.
[0092] A photoresist is coated on the upper surface, and after exposure and development, a patterned mask is formed, exposing part of the upper surface. Then, the metal interconnect board is dry-etched to remove the metal in the exposed areas, forming an array structure. This includes multiple metal interconnect layer units, each with a shape close to a trapezoid. Viewed from above, multiple parallel metal interconnect layer units can be seen, and grooves are formed between adjacent units. Viewed from the side, the metal interconnect layer units appear trapezoidal, with a groove linewidth of 8 μm and an aspect ratio of 8:1. Figure 1 As shown, the metal interconnect layer unit includes a first layer 1, a second layer 2, and a third layer 3, which are stacked sequentially and are Ti layer, Al layer, and Ti layer, respectively.
[0093] S2: Preparation of electrolyte Prepare an alcohol-based solvent by mixing isopropanol and water in a volume ratio of 65:35. Add titanium tetrachloride, ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), and ethylene glycol in a molar ratio of 1:2:4:50 to the alcohol-based solvent to prepare an electrolyte. The electrolyte contains Ti... 4+ The concentration of the electrolyte was 0.2 mol / L. The electrolyte was stirred thoroughly for 2 hours in a warm water bath at 40℃ to obtain a clear and transparent electrolyte containing titanium ions that could be stored for more than 48 hours, with a pH value of approximately 4.2.
[0094] S3: The array structure obtained in S1 is placed in the electrolyte prepared in S2. The aluminum layer in the metal interconnect unit is electrically connected to the power supply as the cathode of the electrolysis reaction. The conductivity can be controlled by the circuit set in the groove. A Pt electrode is also set in the electrolyte as the anode of the electrolysis reaction and is also electrically connected to the power supply. Ultrasonic waves are continuously applied to the electrolyte during the entire electrolysis process, with an average power of 50 W and an average frequency of 3 MHz.
[0095] The voltage applied to the cathode by the power source varies periodically, and each cycle includes the following: First negative voltage (nucleation stage): 0.15 s, -2.5 V, average current density approximately -25 mA / cm² 2 ; Second negative voltage (growth stage): 0.4 s, -1.2 V, average current density approximately -12 mA / cm² 2 ; Positive voltage (desorption stage): 0.2 s, +0.8 V, average current density approximately +8 mA / cm² 2 ; A total of 50 cycles are performed.
[0096] Furthermore, the power supply employs pulsed current, with a single forward pulse current width of 8 ms and a turn-off period width of 10 ms, and a single reverse pulse current width of 12 ms. The waveforms of the pulsed currents during the nucleation and growth stages can be found in the reference diagrams. Figure 4 As shown, the pulse current during the desorption phase is mainly positive pulse.
[0097] S4: Add inhibitors After 30 cycles of the applied voltage, a layer of loose and porous Ti nanoclusters had been deposited on the sidewalls of the Al layer. At this point, thiomalic acid was added to the electrolyte to achieve a concentration of 0.1 mol / L, and the electrolysis system was immersed in an 85°C water bath. Electrolysis continued, and an alloy layer 4 gradually formed on the sidewalls of the aluminum layer. Figure 4 As shown in the figure. During the process, the dielectric constant of the electrolyte was monitored. When the dielectric constant reached 25, the co-deposition of titanium and aluminum ions automatically terminated. Finally, the photoresist was removed, yielding a metal interconnect layer with alloyed sidewalls, the structure of which is shown in the figure. Figure 2 As shown, it includes several metal interconnect layer units with alloyed sidewalls. Each unit includes a first layer 1, a second layer 2, and a third layer 3 stacked sequentially along the thickness direction. An alloy layer 4 is also provided on the sidewall of the second layer 2.
[0098] Example 2 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer. The only difference from Embodiment 1 is that the metal interconnect layer is changed from a Ti-Al-Ti layer to a Mo-Al-Mo layer, and the titanium tetrachloride used to prepare the electrolyte is changed to molybdenum pentachloride. All other steps are the same.
[0099] Example 3 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer, which differs from Embodiment 1 only in that titanium tetrachloride used in preparing the electrolyte is replaced with titanium trichloride. All other steps are the same.
[0100] Example 4 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer, which differs from Embodiment 1 only in that triethanolamine (TEA) is not added in step S2. All other steps are the same.
[0101] Example 5 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer, which differs from Embodiment 1 only in that ethylenediaminetetraacetic acid (EDTA) is not added in step S2. All other steps are the same.
[0102] Example 6 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer. The only difference from Embodiment 1 is that in step S2, ethylenediaminetetraacetic acid (EDTA) and triethanolamine (TEA) are not added; instead, citric acid, in the total molar amount of both, is added. All other steps are the same.
[0103] Example 7 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer. The only difference from Embodiment 1 is that the solvent in step S2 is only water, without the addition of isopropanol or the preparation of an alcohol-based solvent. All other steps are the same.
[0104] Example 8 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer, which differs from Embodiment 1 only in that thiomalic acid in step S4 is replaced with thiosalicylic acid. All other steps are the same.
[0105] Example 9 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer. The only difference from Embodiment 1 is that in step S3, only a negative voltage is applied to the cathode, excluding positive voltage, and the pulse current is adjusted accordingly. All other steps are the same.
[0106] Example 10 This embodiment provides a method for alloying the sidewalls of a metal interconnect layer. The only difference from Embodiment 1 is that pulsed current is not used in step S3. During the application of the first negative voltage, the second negative voltage, and the positive voltage, the same current density and the same direction of current are maintained in each stage. All other steps are the same.
[0107] Comparative Example 1 This comparative example provides a method for alloying the sidewalls of a metal interconnect layer, which differs from Example 1 only in that thiomalic acid is not added in step S4.
[0108] Comparative Example 2 This comparative example provides a method for alloying the sidewalls of a metal interconnect layer. The difference from Example 1 is that after completing step S1, a sputtering deposition method is used to first deposit a small amount of Al on the sidewalls of the Al layer at 350°C, and then deposit a TiAl3 alloy. When the alloy layer thickness reaches 0.5 μm, the deposition is stopped, and the alloying of the sidewalls is completed.
[0109] The differences between Examples 1 to 10 and Comparative Examples 1 to 2 are shown in Table 1.
[0110]
[0111] Relevant performance tests and results analysis 1. Dielectric constant monitoring The dielectric constant at the end of each case reaction is recorded in Table 1 above.
[0112] 2. Sidewall alloying effect testing 2.1 Alloy Composition Verification Phase analysis of the sidewall alloy layers in each embodiment and comparative example was performed using XRD and XPS. The results showed that the second sidewall layer in each embodiment formed an alloy of the first and second metal layers. The test results for each alloy are recorded in Table 1. The high-resolution XPS spectrum of Ti 2P in Example 1 is shown below. Figure 5 As shown, two distinct peaks appear at binding energies of approximately 456.1 eV and 462.0 eV, corresponding to Ti 2P, respectively. 3 / 2 and Ti 2P 1 / 2 Furthermore, the binding energies of these two peaks are slightly shifted compared to pure metallic Ti (453.8 eV and 461.0 eV), indicating that Ti is in an alloy state (Ti-Al bond). Meanwhile, there are no significant peaks at higher binding energies (approximately 458.5 eV and 464.3 eV), indicating a very low degree of oxidation of surface Ti, i.e., the TiO2 peak is weak or absent. This suggests that surface Ti exists primarily in a metallic state and has formed an alloy with Al, rather than existing as an oxide.
[0113] The high-resolution XPS spectrum of Al 2P in Example 1 is shown below. Figure 6 As shown, the main peak is located at approximately 71.8 eV, corresponding to the Al-Ti bond (alloyed Al); at approximately 74.2 eV, there is a small peak, which is Al2O3, indicating that the Al element on the alloy surface is slightly oxidized in air; 2.2 Analysis of Alloy Layer Morphology and Thickness The morphology and thickness of the sidewall alloy layer in each embodiment and comparative example were analyzed by SEM testing, and the degree to which the alloy layer covered the second sidewall was calculated. These test results are recorded in Table 1.
[0114] The results showed that in Examples 1-3 and Example 8, an alloy could be formed on the second layer sidewall to protect the second layer and alleviate the problem of sidewall corrosion.
[0115] In Example 4, the absence of TEA resulted in insufficient inhibition of titanium ion hydrolysis, leading to slight turbidity in the electrolyte preparation and a slight decrease in the quality of the alloy layer formed.
[0116] In Example 5, the absence of EDTA also resulted in insufficient inhibition of titanium ion hydrolysis, leading to slight turbidity when preparing the electrolyte and a slight decrease in the quality of the alloy layer formed.
[0117] It is evident that the simultaneous addition of TEA and EDTA to the electrolyte is beneficial for complexing titanium ions and alleviating their hydrolysis reaction.
[0118] In Example 6, the complexing agent was replaced with citric acid. Due to its weaker complexing ability, the inhibition effect of titanium ion hydrolysis decreased, the electrolyte became slightly turbid when prepared, and the quality of the alloy layer formed also decreased slightly.
[0119] In Example 7, isopropanol was not added, and a small amount of ethylene glycol could not form an alcohol-based solvent, resulting in a decrease in the inhibition effect of titanium ion hydrolysis. Slight turbidity appeared when preparing the electrolyte, and the organic light-emitting material layer under the metal interconnect layer swelled.
[0120] In Example 9, only a negative voltage was applied, which resulted in no desorption process during the electrolytic treatment. The resulting alloy layer was not smooth enough, and the electrolyte was prone to concentration polarization during the electrolysis process. A small number of voids appeared in the alloy layer, leading to a decrease in quality.
[0121] In Example 10, pulsed current is not used. After etching, the Al layer sidewall surface contains many fine trenches. During the electrolytic process, metal ions tend to accumulate at the trench openings, resulting in insufficient coverage inside the trenches, low coverage of the sidewall alloy layer, poor continuity, and a tendency for voids to occur.
[0122] In Comparative Example 1, although the alloy layer coverage was high thanks to the complexing agent and electrolysis method, the electrolytic deposition reaction could not terminate on its own due to the lack of inhibitors. The alloy layer on the Al sidewall continued to grow, and the thickness of the alloy layer in all metal interconnect units exceeded the standard, affecting the routing within the grooves and subsequent electrical connections with the Al layer. Without inhibitors, the alloy layer thickness must be continuously monitored during the electrolysis process to stop the current supply in time, which significantly impacts production efficiency.
[0123] In Comparative Example 2, the traditional sputtering deposition technique was used, which caused thermal damage to the OLED organic light-emitting material layer, affecting the display effect.
[0124] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for alloying metal surfaces, characterized in that, Includes the following steps: An acidic electrolyte containing a first metal ion is prepared, and the electrolyte is electrolyzed using a second metal as the cathode. During the electrolysis process, an inhibitor is added to the electrolyte; The inhibitor includes thiocarboxylic acid materials, and the reducing power of the second metal is higher than that of hydrogen.
2. The metal surface alloying treatment method according to claim 1, characterized in that: The first metal ion includes at least one of titanium ions and molybdenum ions; and / or, The second metal includes aluminum; and / or, When the total electrolysis treatment time is 60% to 70%, the inhibitor is added to the electrolyte; and / or, The thiocarboxylic acid materials include at least one of thiomalic acid, thiosalicylic acid, and mercaptosuccinic acid; and / or, The electrolysis process further includes the step of applying ultrasound to the electrolyte; and / or, When an inhibitor is added to the electrolyte, the concentration of the inhibitor in the electrolyte is 0.05 mol / L to 0.15 mol / L; and / or, After adding an inhibitor to the electrolyte, the electrolyte is heated to a temperature of 55°C to 90°C.
3. The metal surface alloying treatment method according to claim 1 or 2, characterized in that, The first metal ion includes titanium ions, and the prepared electrolyte satisfies at least one of the following characteristics: (1) The concentration of titanium ions is 0.05 mol / L to 0.3 mol / L; (2) The electrolyte includes a complexing agent and an alcohol solvent; (3) The pH value of the electrolyte is 4.0 to 4.5; (4) The solute in the electrolyte includes at least one of titanium tetrachloride and titanium trichloride.
4. The metal surface alloying treatment method according to claim 3, characterized in that: The complexing agent includes at least one selected from ethylenediaminetetraacetic acid, triethanolamine, citric acid, and citrate; and / or, The alcohol solvent includes at least one of isopropanol and ethylene glycol; and / or, The molar ratio of the first metal ion to the complexing agent is 1:(4-8.5).
5. The metal surface alloying treatment method according to any one of claims 1, 2, or 4, characterized in that, The electrolysis process includes a periodic energizing process, each cycle comprising sequentially applying a first negative voltage, a second negative voltage, and a positive voltage, and satisfying at least one of the following characteristics: (1) The absolute values of the first negative voltage, the second negative voltage, and the positive voltage decrease sequentially; (2) The duration of applying the first negative voltage is 0.1 s to 0.3 s; (3) The duration of applying the second negative voltage is 0.2 s to 0.6 s; (4) The duration of applying the positive voltage is 0.1 s to 0.3 s; (5) The periodic power-on process includes 40 to 60 cycles.
6. The metal surface alloying treatment method according to any one of claims 1, 2, or 4, characterized in that, The current type for the electrolytic treatment includes pulsed current, and the pulsed current satisfies at least one of the following characteristics: (1) Peak current density is -27 mA / cm 2 ~-23 mA / cm 2 ; (2) The width of a single pulse current is 8 ms to 12 ms; (3) The duty cycle of the reverse pulse is 30% to 70%.
7. A method for alloying the sidewalls of a metal interconnect layer, characterized in that, Includes the following steps: A metal interconnect layer cell to be processed is provided, the metal interconnect layer cell to be processed comprising a first layer, a second layer and a third layer stacked sequentially along the thickness direction; The sidewalls of the metal interconnect layer unit to be treated are processed according to the metal surface alloying treatment method as described in any one of claims 1 to 7; The first layer and the third layer contain the metal corresponding to the first metal ion, and the second layer contains the second metal.
8. The method for alloying the sidewalls of the metal interconnect layer according to claim 7, characterized in that: The thickness of the first layer is 0.05 μm to 0.2 μm; and / or, The thickness of the second layer is 0.2 μm to 1 μm; and / or, The thickness of the third layer is 0.05 μm to 0.2 μm; and / or, The metal interconnect layer unit to be processed is obtained by etching a metal interconnect board.
9. A metal interconnect layer, characterized in that: It includes several sidewall-alloyed metal interconnect layer units, the sidewall-alloyed metal interconnect layer units being... Obtained by the metal interconnect layer sidewall alloying treatment method as described in claim 7 or 8; The sidewall alloyed metal interconnect unit includes a first layer, a second layer, and a third layer stacked sequentially along the thickness direction; Furthermore, an alloy layer is provided on at least the sidewall of the second layer.
10. A display panel, characterized in that: Includes the metal interconnect layer as described in claim 9.